Simultaneous Extraction And Stripping Of Cu(II) Ions Through Vegetable Oil-Based Bulk Liquid Membrane - Chang, Siu Hua (2011)
This research aims to examine the feasibility of replacing the classical petroleum-based organic solvents, which are non-renewable and invariably toxic, with the vegetable oil-based ones, that are more renewable and environmentally benign, as the membrane phase of a bulk liquid membrane (BLM) for simultaneous extraction (removal) and stripping (recovery) of Cu(II) ions in a single unit. The liquid-liquid extraction results revealed that soybean oil-based organic solvent (soybean oil loaded with di-2-ethylhexylphosphoric acid (D2EHPA) (extractant (carrier)) and tributylphosphate (TBP) (phase modifier)) and sulphuric acid (H2SO4) of 1.5 M were the most suitable organic solvent and efficient stripping agent,